Workforce, succession planning, and optimism for the future among Swiss general practitioners with additional training in complementary medicine in 2016: A nationwide cross-sectional study - Erschena Reichle; Martin Frei-Erb; Sven Streit (PLoS ONE, 2026)
The shortage of general practitioners (GPs) and the aging workforce of established GPs in Switzerland are persistent. Furthermore, data on GPs with additional training in complementary medicine (CM) are lacking. This study aimed to obtain information on GPs with training in CM. A nationwide cross-sectional study was conducted using an anonymous online survey to assess the demographics, practice structures, workloads, and future perspectives. The participants were members of four CM societies representing doctors with CM certificates (n = 1,067) in traditional Chinese medicine/acupuncture (TCM/A), homeopathy (HOM), anthroposophical medicine, and phytotherapy. Overall, 206 GPs were included and divided into three groups: TCM/A (n = 73), HOM (n = 76), and others (n = 57). Most participants were male, and approximately half worked in double or group practices. They worked an average of 36 h per week, which had decreased by 13 h over the past 5 years, with plans for further reduction in the future. Approximately 18% planned to continue working beyond the retirement age, and 4% wanted to retire before that age. The majority expressed optimism about the future of CM in Swiss healthcare but less for individual CM disciplines. Compared to the 2015 Swiss Workforce Study, more CM GPs were female, worked less often in group practices, made fewer house calls, and were more optimistic about the future. CM-GPs in Switzerland face the same challenges as conventional GPs. National action and collaboration are needed to improve working conditions and to address the trend towards part-time work and an ageing workforce to safeguard healthcare for the population.